2022
DOI: 10.3389/fpubh.2022.993728
|View full text |Cite
|
Sign up to set email alerts
|

Myopia progression and associated factors of refractive status in children and adolescents in Tibet and Chongqing during the COVID-19 pandemic

Abstract: ObjectivesTo investigate myopia progression and associated factors of refractive status among children and adolescents in Tibet and Chongqing in China during the COVID-19 pandemic.MethodsA population-based cross-sectional study was conducted to compare rates of myopia and high myopia, axial length (AL), spherical equivalent (SE), outdoor activity time, digital device use, and frequency of visual examinations for children and adolescents affected by myopia in Chongqing and Tibet in 2021.ResultsA total of 2,303 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Epidemiological data show that the prevalence of keratoconus, pterygium, dry eye disease, cataract and strabismus is significantly higher in the highlands than in the lowlands2 6–9 and the cornea of the highlanders is thinner than that of the lowlanders 10 11. Our previous study also found that the prevalence of myopia among children and adolescents in Tibet was lower than that in the plains 12. However, it is unclear whether ocular biometry is associated with myopia prevalence between high and low altitude populations with different levels of UVR exposure.…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…Epidemiological data show that the prevalence of keratoconus, pterygium, dry eye disease, cataract and strabismus is significantly higher in the highlands than in the lowlands2 6–9 and the cornea of the highlanders is thinner than that of the lowlanders 10 11. Our previous study also found that the prevalence of myopia among children and adolescents in Tibet was lower than that in the plains 12. However, it is unclear whether ocular biometry is associated with myopia prevalence between high and low altitude populations with different levels of UVR exposure.…”
Section: Introductionmentioning
confidence: 49%
“…Furthermore, our analysis of altitude subgroups revealed a decrease in the mean value of AL with increasing altitude. Although information regarding outdoor activities was not collected in this study for both groups, our previous research demonstrated that children and adolescents in Tibet spend more time outdoors than those in Chongqing,12 which may be synergistic with stronger UVR intensity and longer average daily sunshine in Tibet in slowing myopia progression.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Java-Bali is considered more urban than other areas in Indonesia archipelago. Living in urban area has been identi ed as an established environmental factor which promotes the progression of myopia through higher economic and civilization standards [18][19][20] . Studies comparing myopia prevalence pre and during pandemic also observed a signi cant increase in urban students [7,17,19] .…”
Section: Higher Myopia Progression In Java Bali Other Centersmentioning
confidence: 99%
“…5,6 It has been shown that macular structure change negatively affected final surgical outcomes. 7 FLACS is an innovative technology which could decreased phacoemulsification time and energy by automating the formation of corneal incisions and flaps, continuous curvilinear capsulotomy, and lens fragmentation. It may offer benefit for cataract patients with other complicated ocular diseases such as vitreous abnormalities.…”
mentioning
confidence: 99%